Proceso de Distribución de los Productos de Big Cola Ciudad de Babahoyo - zamora Jimenez, Lilibeth Denisse (2018)
BIG COLA company has managed to be a multinational that is dedicated to the production, distribution and marketing of mass consumption products that are in constant and permanent growth with successful presence in various countries in Latin America, this company is of Peruvian nationality was created in the decade of 1980 by five brothers of last name Añaños, in the year 2000 was introduced in the Ecuadorian market where at present it counts with more than 200 distributors at national level, one of these distributors is located in the City of Babahoyo in the bypass operating since 2005 and is made up of 25 workers. By having a matrix in the city of Guayaquil called AJE, which is responsible for supervising all the activities of distributors in nearby cities, the lack of control and compliance in terms of supervision of supply and distribution of the product, generating in the distributor of the city of Babahoyo copo interest at the time of distributing the different products to the micro companies considering these as stores and grocery stores